Palestine as a Symbol of Justice: Identity, Faith, and Resistance in Indonesian Muslim Narratives (Palestine Issues on Indonesian Society, 2025)
This paper investigates how Palestinian issues are framed within Indonesian Muslim narratives, where Palestine serves not only as a symbol of resistance but also as a symbol of justice and solidarity in the context of Muslim identity. The study analyzes religious sermons, political discourses, and literary works produced by Indonesian Muslim scholars and activists, focusing on the symbolic role of Palestine in Islamic thought and Indonesian Muslim identity. The research identifies how Palestinian resistance is depicted as part of the broader Islamic struggle for justice, often positioned within the theological and historical frameworks of Islamic teachings on oppression, resistance, and justice. By examining narratives that blend faith-based principles with political advocacy, the paper sheds light on how Indonesian Muslims view the Palestinian cause as part of a larger, global Islamic movement for justice. This study contributes to the understanding of how political identity and religious faith intersect in the Indonesian context and how the Palestinian cause is integrated into local political and religious discourses.